Chronic Rhinosinusitis with Polyps Is Characterized by Increased Mucosal and Blood Th17 Effector Cytokine Producing Cells - Miljkovic, Dijana; Psaltis, Alkis J.; Wormald, Peter J.; Vreugde, Sarah (Frontiers in Physiology, 2017)
Background: Recent studies have implied a role for Th17 cells in CRS with nasal polyps (CRSwNP) patients. However, the capacity of these cells to produce Th17 cytokines is still unknown. Here we sought to quantify IL-17A, IL-17F, IL-21, and IL-22 cytokines produced by Th17 cells in mucosal tissue and peripheral blood of CRSwNP, CRS without nasal polyps (CRSsNP) and control patients. Methods: Samples were prospectively collected from CRS patients and non-CRS controls. We used flow cytometry to characterize the Th17 cells and their cytokines in sinonasal tissue and peripheral blood. Results: A total of 36 patients were recruited to the study. CRSwNP patients had significantly more tissue IL-17A (9.53 ± 2.71 vs. 1.11 ± 0.43 vs. 0.77 ± 0.07), IL-17F (4.96 ± 1.48 vs. 0.88 ± 0.31 vs. 0.56 ± 0.04), IL-21 (5.55 ± 2.01 vs. 1.60 ± 0.71 vs. 1.53 ± 0.55) and IL-22 (4.73 ± 1.58 vs. 0.70 ± 0.28 vs. 0.88 ± 0.26) producing Th17 cells compared to CRSsNP and control mucosa per mg of tissue, respectively. Allergic CRSwNP patients had decreased numbers of IL-21 producing Th17 cells compared to non-Allergic CRSwNP. (1.69 ± 0.57 vs. 9.41 ± 3.23) per mg of tissue, respectively (Kruskal-Wallis p < 0.05). Conclusion: In summary our study identified increased numbers of IL-17A, IL-17F, IL-21 and IL-22 positive Th17 cells in CRSwNP patient polyps and peripheral blood suggesting an altered activation state of those cells both locally and systemically. Atopic CRSwNP had decreased amounts of tissue Th17 cell derived IL-21 implying a potential protective role for IL-21 in CRSwNP allergic inflammation.